Results of a modified Delphi consensus on the optimal testing pathway for oesophago-gastric cancer care in the UK - Philippe Taniere; Manuel Rodriguez-Justo; Naureen Starling; Wasat Mansoor; Thomas Bird; Martin Eatock (BMJ Open)
Objective To develop expert consensus on the optimal testing pathway for oesophago-gastric (OG) cancer care.Methods and analysis The process followed a modified Delphi methodology to develop consensus on the optimal testing pathway for OG cancer care. In November 2023, a review of available literature on the topic of OG cancer was conducted. The results of this review informed a steering group discussion on the barriers and opportunities within the OG testing pathway. Six domains of focus were agreed on and used to develop. 36 agreed statements were developed into a Likert survey, which was distributed by a third party (M3 Global Research). Completed surveys were analysed to produce an arithmetic agreement score for each statement. The results were then reviewed by the steering group to agree on any recommendations and conclusions.Results A total of 50 responses were received from consultant oncologists (n=25), pathologists (n=15), specialist oncology pharmacists (n=5) and specialist oncology nurses (n=5). Consensus was achieved in 35/36 statements (97%). The steering group agreed on a commentary on the results and a series of recommendations for best-practice testing in OG cancer. Given the level of agreement and that the stopping criteria were met, it was decided not to undertake further Delphi rounds.Conclusion The recommendations support the use of a reflex testing approach for human epidermal growth factor receptor 2, programmed death ligand 1 and microsatellite instability high/mismatch repair deficiency in patients diagnosed with OG cancer who are suitable for treatment with targeted therapy.